Novel Oxidation of Hydrogen Sulfide by Dimethyl Sulfoxide in Presence of b-Cyclodextrin - Yang, Xiaoxia; Zhang*, Jianbin; Chang, Yan; Li, Qiang (Asian Journal of Chemistry, 2014)
Dimethyl sulfoxide is used as an oxidizing agent to oxidize hydrogen sulfide to solid sulfur at room temperatures and normal pressures, in which, b-cyclodextrin plays an important role in this reaction. In this work, when GC-MS, SEM and FTIR spectroscopic techniques were used for inspection of spectral changes of b-cyclodextrin, dimethyl sulfoxide solution with increasing H2S concentration, the results suggest that H2S was oxidated by dimethyl sulfoxide in the presence of b-cyclodextrin and dimethyl sulfide, water, and sulfur can be identified. The results of this work can be used to provide important reaction mechanism of H2S with dimethyl sulfoxide in the presence of b-cyclodextrin with potential industrial application of b-cyclodextrin-dimethyl sulfoxide solution.